Teaching and using remote sensing in argentine archaeology : evaluating the University of Buenos Aires curriculum and the graduation theses of the last decade - (:unkn) unknown (Archaeopress, 2006)
Remote sensing in archaeology can be addressed from three different angles: 1) Creation of technologies (developers), 2) Transmission of knowledge (teachers) and 3) Use of technologies (researchers). In this paper, I will deal with remote sensing education and research because they are still underdeveloped in argentine archaeology. These two areas are closely related because we need to acquire knowledge before we can use it.
Fil: Kligmann, Débora M.. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Ciencias Antropológicas. Sección Arqueología; Argentina.
La versión digital aún no está disponible.
Keywords: Arqueología